2020
DOI: 10.3389/fcell.2020.586578
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage and Antioxidant Defense in Ferroptosis

Abstract: Many new types of regulated cell death have been recently implicated in human health and disease. These regulated cell deaths have different morphological, genetic, biochemical, and functional hallmarks. Ferroptosis was originally described as a carcinogenic RAS-dependent non-apoptotic cell death, and is now defined as a type of regulated necrosis characterized by iron accumulation, lipid peroxidation, and the release of damage-associated molecular patterns (DAMPs). Multiple oxidative and antioxidant systems, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
230
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 354 publications
(236 citation statements)
references
References 120 publications
(166 reference statements)
6
230
0
Order By: Relevance
“…Our results indicated that iron overload played detrimental effects in OA progression, however, how excess iron damages chondrocytes under OA pathogenic conditions remains unknown. Excess free iron could act as a catalyst to produce large amount of ROS and lead to accumulation of lipid peroxides and ferroptosis (Kuang et al, 2020). Ferroptosis is a newly identified iron dependent cell death and we speculate that ferroptosis is involved in iron overload induced chondrocytes apoptosis.…”
Section: Figure 6 | Inhibition Of Dmt1 Restored Il-1β Induced Chondromentioning
confidence: 81%
“…Our results indicated that iron overload played detrimental effects in OA progression, however, how excess iron damages chondrocytes under OA pathogenic conditions remains unknown. Excess free iron could act as a catalyst to produce large amount of ROS and lead to accumulation of lipid peroxides and ferroptosis (Kuang et al, 2020). Ferroptosis is a newly identified iron dependent cell death and we speculate that ferroptosis is involved in iron overload induced chondrocytes apoptosis.…”
Section: Figure 6 | Inhibition Of Dmt1 Restored Il-1β Induced Chondromentioning
confidence: 81%
“… 56 GSH scavenge ROS and free radicals to protect cells from oxidative damage. 57 Main antioxidant enzymes are GPx, SOD, and CAT. GPx is mainly responsible for removal of hydroperoxides, hence, it may protect membranes, lipids, and proteins from oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Excess of free reactive iron can cause various types of cell death, including a recently recognized type, ferroptosis. Although the core molecular effector of ferroptosis is unclear, ferroptosis is induced by the activation of iron-dependent lipid peroxidation ( Kuang et al, 2020 ). Significant progress has been made in dissecting the mechanisms that lead to lipid peroxidation and how antioxidant systems or stress proteins regulate ferroptosis.…”
Section: Discussionmentioning
confidence: 99%